Literature Review Teori Transcultural Nursing Madeleine Leininger - Susi Agustina Lasmaida; Blacius Dedi (International Journal Labs, 2024)
Transcultural nursing is the study and practice of nursing that focuses on the similarities and differences in cultural values, beliefs, and actions, both individuals and groups. The goal is to provide nursing actions that are based on universal culture and specific culture, both in providing health promotion, and helping patients deal with unpleasant conditions, illness, death where culturally meaningful. This research uses a literature study method analyzed from several journals, research results, using internet media related to the topic taken. The results showed that transcultural nursing is a nursing care process that is focused on individuals and groups to maintain, improve healthy behavior according to cultural background. The study of nursing care in a cultural context is needed to bridge the differences in knowledge possessed by nurses with patients or clients. Transcultural nursing diagnoses can identify actions needed to maintain a culture that matches health goals, form a new culture that is appropriate to health, or even replace a culture that is not appropriate to health into a new culture. The planning and implementation of the transcultural nursing process is made after the nurse understands the cultural background of the patient or client, so that the actions carried out can be in accordance with the client's culture and health goals are achieved. The evaluation of transcultural nursing care is closely attached to the planning and implementation of the transcultural nursing care process. This theory can be used in providing nursing care by considering aspects of culture, values, norms, and religion. This theory can be used to complement other conceptual theories in nursing care.